The Lived Experience of Persons with Spinal Cord Injuries Engaging in Remote Work: A South African Perspective - Alicia Swart; Jerome Peter Fredericks; Lee-Ann Juliana Jacobs-Nzuzi Khuabi (Occupational Therapy International)
In South Africa, traumatic SCI cases are disproportionately high in comparison to other countries. Low retention and maintenance of work for persons with SCIs are further exasperated by structural barriers and societal stigma. Persons with SCIs have the ability to contribute to the labour market, and doing so could lead to the improvement of their quality of life and socioeconomic status. Addressing engagement in work as a meaningful occupation for persons with SCIs is essential to mitigate occupational risk factor and uphold occupational justice. Currently, there is a paucity of literature on remote work practices for persons with SCIs. This study seeks to add to this body of knowledge to increase occupational therapists’ awareness of the possibility of remote work to facilitate the inclusion of persons with SCIs in the open labour market. This phenomenological study explored the facilitators and barriers of engaging in remote work in the open labour market for paid employment, as experienced by persons with SCI within the Gauteng metropole, South Africa. Data was collected via semistructured interviews from four participants and analysed thematically. Four themes were generated from the data: (1) intrinsic facilitators of remote work, (2) extrinsic facilitators of remote work, (3) intrinsic barriers to remote work, and (4) extrinsic barriers to remote work. Remote work can be utilised to include persons with SCIs in their chosen occupation of work and is a holistic and client-centred approach. Remote work should not be seen as the sole method of inclusion but can also be used in conjunction with traditional office work to accommodate persons with SCIs in the workplace.